Odd-numbered fatty acids in type 2 diabetes mellitus - Janeček, Radim; Špryncová, Martina; Čegan, Alexander (University of Pardubice, 2018)
This work deals with the study of lipid metabolism in type 2 diabetics focusing on the changes in odd-numbered fatty acid concentrations. Diabetes mellitus is a syndrome of metabolic disorders in which the concentration of insulin and its secretion are impaired. It indicates an impaired metabolism of glucose, lipids, and proteins. The main goal of this work was to measure concentrations of odd-numbered fatty acids (ONFA) in healthy individuals and in patients with type 2 diabetes mellitus and to compare the concentrations between both groups by using statistical methods. Plasma samples were deproteinized and lipids were extracted into organic solvents. Thin layer chromatography was used to separate 5 lipid fractions. All the lipid fractions were derivatized into fatty acid methyl esters and analyzed by a gas chromatograph. ONFA are minor group of the fatty acids and their concentrations are lower in type 2 diabetes mellitus. The most significant changes in concentrations were registered for tridecanoic and pentadecanoic acid.
Keywords: diabetes mellitus; gas chromatography; lipid metabolism; odd-numbered fatty acids